The long-term clinical outcomes of intravascular ultrasound-guided versus angiography-guided coronary drug eluting stent implantation in long de novo coronary lesions: A systematic review and meta-analysis - Wang, Shen; Liang, Changzai; Wang, Yue; Sun, Shuaifeng; Wang, Yue; Suo, Min; Ye, Maomao; Li, Xinjian; Liu, Xinyan; Zhang, Meng; Wu, Xiaofan (Frontiers in Cardiovascular Medicine, 2022)
Background: No meta-analysis has been conducted to compare the long-term clinical outcomes of intravascular ultrasound (IVUS)-guided versus angiographic-guided drug-eluting stent implantation in patients with long de novo coronary lesions. We attempted to compare the efficacy and safety of IVUS guidance versus angiography guidance in percutaneous coronary intervention (PCI) for long de novo coronary lesions. Methods: We performed a detailed meta-analysis from four randomized controlled trials (RCTs) and one retrospective study to compare long outcomes of IVUS versus angiography in guiding coronary stent implantation with long de novo coronary lesions. Clinical outcomes included major adverse cardiovascular events (MACE), all revascularization, including target lesion revascularization (TLR) and target vessel revascularization (TVR), all myocardial infarction (MI), all-cause death, and stent thrombosis (ST). Cochrane Library, Embase, PubMed, Web of Science were searched. Results: Four RCTs and one retrospective study were included in our study with 3349 patients (IVUS guidance= 1708; Angiography guidance = 1641). At mean follow-up of 2 years, the incidence of MACE, all myocardial infarction, all revascularization and stent thrombosis were significantly lower in IVUS-guided DES implantation of patients with long de novo coronary lesions than in angiography-guided patients; MACE (OR 0.41; 95% confidence interval [CI], 0.29–0.58; p＜0.00001), All myocardial infarction (OR 0.23; 95% CI, 0.09–0.58; p = 0.002), All revascularization (OR 0.48; 95% CI, 0.36–0.66; p＜0.00001), Stent thrombosis (OR 0.32; 95% CI, 0.11–0.89; p = 0.03). There was no significant difference in all-cause mortality between the two groups (OR 0.82; 95% CI, 0.55–1.23; p = 0.34). Conclusions: During mean follow-up of 2 years, the incidence of MACE, stent thrombosis, all myocardial infarction and revascularization in patients with long de novo coronary lesions under IVUS-guided PCI were significantly lower than angiography-guided PCI, and there were no statistically significant differences in all-cause mortality.